Focke Wulf 190 defending the Reich, 1943-1945 - Jessen, Morten (London : Mechanicsburg, Pa. : Greenhill Books ; Stackpole Books, 2000)
From the spring of 1942 until the end of the war, Germany was pounded by night and by day by Allied aircraft. A key element of the German defenses was the Fw 190, a rugged, well armed and reliable machine. This book details the Fw 190 and its variants in the crucial years of 1943/45, and presents rare photos of the planes, their crews, and their combat missions.
Includes bibliographical references (p. 8).
76743
Keywords: World War -- Aerial operations, German. -- 1939-1945; Focke-Wulf 190 (Fighter planes) -- History